High-loaded single Cu atoms decorated on N-doped graphene for boosting Fenton-like catalysis under neutral pH. Issue 27 (2nd July 2020) - Wu, Qianyuan; Wang, Jin; Wang, Zhiwei; Xu, Yalan; Xing, Zhihui; Zhang, Xinyang; Guan, Yuntao; Liao, Guangfu; Li, Xinzheng
Abstract : A single-atom Cu dispersed on N-doped graphene with ultrahigh Cu loading of 5.8 wt% was prepared for boosting the degradation of contaminants. Abstract : Here, single-atom Cu dispersed on N-doped graphene (Cu-SA/NGO) with relatively high Cu loading of 5.8 wt% was prepared for boosting the degradation of contaminants. This is the highest value yet reported for dispersion of single metal atoms on graphene. Atomically dispersed CuN4 moieties were confirmed by high-angle annular dark field-scanning transmission electron microscopy and X-ray absorption fine structure spectroscopy. The prepared Cu-SA/NGO shows remarkable activity and stability in the degradation of various organic contaminants at neutral pH. This excellent performance is mainly ascribed to the large number of active sites obtained from high single-atom-Cu loading. Density functional theory calculations confirmed that CuN4 moieties serve as the active sites, with low energy barriers for hydroxyl radical (˙OH) generation. These supported single-atom catalysts (SACs) catalyze the heterogeneous Fenton reaction via proton-mediated H2 O2 -homolytic pathway. This work offers a new method for fabricating various SACs with high loading levels for catalytic oxidation reactions.